(untitled) (Scientia Agropecuaria, 2023)
The aim of this study was to analyze the relationships between the Visual Evaluation of Soil Structure (VESS) and soil properties that make its adoption widely used in agriculture. For this, 25 papers related to the VESS (2009-2022) were considered, and information on the soil property: bulk density (BD), total soil porosity (TP), soil penetration resistance (PR), macroporosity, microporosity, soil organic carbon (SOC), and mean weight diameter of stable aggregates (MWD). The sample size (n=120 cases), and the correlation coefficient were extracted. A meta-analysis was carried out to obtain a global measure of the correlation between the VESS and soil properties. In the first instance, a fixed effects model was fitted for the correlation (effect size as the response variable in the meta-analysis). Subsequently, a random effects model was fitted for the correlation, followed by a subgroup analysis according to soil properties, due to the presence of high heterogeneity. The overall effect (average correlation coefficient) of the fitted random effects model was 0.31 with a confidence interval of 0.22-0.41. The heterogeneity between studies was high (I 2: 94%) and statistically significant (p<0.001). Although it is moderate, the average correlation in practical terms may be sufficient. There were significant differences in some average correlations of some categories, such as BD, PR, TP, and microporosity. The weights reported for the BD, SOC, and PR were 29.7%, 16.4%, and 14.2%, respectively. The greatest contribution to the global effect of correlation between VESS and soil properties is provided by BD. The VESS is a reliable semi-quantitative method to assess soil quality and could be considered a promising visual predictor of soil physical properties such as BD, SOC, and PR. Periodic evaluation of structural quality should be an important aspect of soil quality management, improving the predictive level of soil properties.